The catholic taste of broad tapeworms - multiple routes to human infection - Waeschenbach, Andrea; Brabec, Jan; Scholz, Tomáš; Littlewood, D Timothy J; Kuchta, Roman (International journal for parasitology, 2017)
Broad tapeworms (Cestoda: Diphyllobothriidea) are the principal agents of widespread food-borne cestodosis. Diphyllobothriosis and diplogonoporosis, caused by members of the genera Diphyllobothrium, Diplogonoporus and Adenocephalus, are the most common fish cestodoses with an estimated 20million people infected worldwide, and has seen recent (re)emergences in Europe due to the increasing popularity of eating raw or undercooked fish. Sparganosis is a debilitating and potentially lethal disease caused by the larvae of the genus Spirometra, which occurs throughout much of the (sub)tropics and is caused by the consumption of raw snakes and frogs, and drinking water contaminated by infected copepods. Both diseases are caused by several species, but the frequency by which the transition to humans has occurred has never been studied. Using a phylogenetic framework of 30 species based on large and small nuclear ribosomal RNA subunits (ssrDNA, lsrDNA), large subunit mitochondrial ribosomal RNA (rrnL) and cytochrome c oxidase subunit I (cox1), we hypothesize that humans have been acquired asaccidental hosts four times across the tree of life of diphyllobothriideans. However, polytomies prevent an unambiguous reconstruction of the evolution of intermediate and definitive host use. The broad host spectrum and the frequency with which switching between major host groups appears to have occurred, may hold the answer as to why accidental human infection occurred multiple times across the phylogeny of diphyllobothriideans. In this study Diplogonoporus is determined to be the junior synonym of Diphyllobothrium. Furthermore, we divide the latter polyphyletic genus into (i) the resurrected genus Dibothriocephalus to include freshwater and terrestrial species including Dibothriocephalus dendriticus, Dibothriocephalus latus and Dibothriocephalus nihonkaiensis as the most common parasites of humans, and (ii) the genus Diphyllobothrium to accommodate parasites from cetaceans including the type species Diphyllobothrium stemmacephalum and Diphyllobothrium balaenopterae n. comb. known also from humans. The non-monophyletic aggregate of marine species from seals is provisionally considered as incertae sedis.
Keywords: potrava z moře (živočišná); mitochondriální geny; nemoci ryb; Humans; Cestode Infections; Phylogeny; RNA helmintů; ryby; Fish Diseases; Systematics; Mitochondrial; Microscopy, Electron, Scanning; Foodborne Diseases; lidé; zvířata; Diphyllobothriosis; Copepoda; Fishes; RNA ribozomální; RNA, Helminth; Nuclear; fylogeneze; mikroskopie elektronová rastrovací; cestodózy; RNA, Ribosomal; Seafood; Taxonomic revision; nemoci přenášené potravou; Bayesova věta; Sparganosis; Animals; Genes, Mitochondrial; Diphyllobothriidea; Bayes Theorem; Cestoda